The Implementation of Reading Aloud in Developing Students' Speaking Skill - Ardhy Supraba; Edi Wahyono; Abdullah Syukur (Institut Agama Islam Negeri Palopo, 2020)
This research focuses on the implementation of reading aloud in developing students’ speaking skill. It aims to find out whether the implementation of reading aloud develops the students’ speaking skill. This research used correlation research design in which questionnaire and speaking test are the instruments of this research. The population of this research is the first semester students of English Language Education Study Program, Faculty of Teacher Training and Education, Cokroaminoto Palopo University. The sample of this research is selected through purposive sampling technique. One class represented as the sample that is class B. The result of this research shows that reading aloud can be effective way in teaching speaking class since there is a significant relationship between reading aloud and the students’ speaking skill. It is determined by p value of 0,027 which is below 0,05. Thus, the implementation of reading aloud significantly contributed to develop students’ speaking skill.